Concept of Sale for the Purposes of the General Tax on Sales - Ruiz de Castilla Ponce, Francisco Javier (2014)
The definition of sale can be determined in several ways depending on the law branch that is studying the sale, however, for tax purposes, the sale takes a different connotation which tries to be elucidated in the current article, in which is taken into account the Tax on the General Sales (IGV) as the resolutions of the Tax Court. Furthermore, it is intended to elucidate the fact that constitutes the sale for IGV in which is called the self-governing of the Taxation Law.